Spectroscopic and thermal characterization in poly(p-phenylene vinylene)/sol-gel silica sample - Pilla, V; Andrade, A. A.; Lima, S. M.; Catunda, T.; Donatti, D. A.; Vollet, D. R.; Ruiz, A. I. (Elsevier B.V., 2003)
The absorption and luminescence spectra for the poly(p-phenylene vinylene)/sol-gel silica with different thermal treatments were measured. A considerable increase in the luminescence was observed for the polymer introduced into SiO2 matrix with thermal treatment at 120 degreesC. The thermal diffusivity of these samples was measured using the thermal lens technique, and the obtained value 3.3 x 10(-5) cm(2)/s (sample treated at 37 degreesC) is practically independent of the thermal treatment (37-150 degreesC). (C) 2003 Elsevier B.V. All rights reserved.
Keywords: PPV; sol-gel; thermal lens technique